2008
DOI: 10.1063/1.2844595
|View full text |Cite
|
Sign up to set email alerts
|

Adaptively biased molecular dynamics for free energy calculations

Abstract: We present an Adaptively Biased Molecular Dynamics (ABMD) method for the computation of the free energy surface of a reaction coordinate using non-equilibrium dynamics. The ABMD method belongs to the general category of umbrella sampling methods with an evolving biasing potential, and is inspired by the metadynamics method. The ABMD method has several useful features, including a small number of control parameters, and an O(t) numerical cost with molecular dynamics time t. The ABMD method naturally allows for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
287
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(290 citation statements)
references
References 30 publications
1
287
0
2
Order By: Relevance
“…This sum gets more and more expensive as the simulation proceeds and the number of Gaussians grows [35]. Usually this is not a problem since, if we exclude the simplest test cases, this effort is incomparably smaller than that of evaluating the force-field.…”
Section: B Metadynamics Implementationmentioning
confidence: 99%
“…This sum gets more and more expensive as the simulation proceeds and the number of Gaussians grows [35]. Usually this is not a problem since, if we exclude the simplest test cases, this effort is incomparably smaller than that of evaluating the force-field.…”
Section: B Metadynamics Implementationmentioning
confidence: 99%
“…Further realizations of grid techniques incorporate adaptive grids where the potential energy is calculated by a polynomial extrapolation on the grid points [51,53], choosing the potential of a close grid point as the biasing potential on the particle [51] or applying cut-off radii for the gaussians [51]. It was also shown that the above mentioned adaptive biased grid approach in its computational cost scales linearly with simulation time in contrast to ordinary metadynamics [47]. Here cubic B-splines are used for the evaluation of the biasing potential on the corresponding grid points.…”
Section: Introductionmentioning
confidence: 99%
“…By comparison to other approaches, it has to be noticed that in recent publications [32,45,46] the usage of umbrella sampled biased probability distributions respectively using histogram reweighting procedures [48] for the correction of free energy landscapes has also been claimed. Even the evaluation of the underlying potential on a grid point has been recently proposed for metadynamics [46] as well as for a closely related adaptive bias molecular dynamics scheme [47]. Both ingredients have also been applied in a grid-based adaptive umbrella sampling scheme [49] over a decade ago and the above mentioned techniques are implemented in common software packages [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…It indicates a typical level of 5−7 kcal/mol above the global minimum in F that is reached within a simulation time of 200 ns at 300 K. In order to explore the conformational space more thoroughly, we selectively perform biased MD simulations, based on the adaptive biasing molecular dynamics (ABMD) scheme. 37 The strategy is to find a biasing potential acting on the glycosidic angles in order to achieve their uniform sampling (Supporting Information, section A3). Pictorially, the free energy landscape is "flooded".…”
Section: ■ Methodsmentioning
confidence: 99%